Spatiotemporal epidemiology and clinical manifestations of two decades of scrub typhus in India: a systematic review and meta-analysis - Amit Sharma; Manju Rahi; Syed Shah Areeb Hussain; Rini Chaturvedi; Hayavadhan Sampath; Bijay R Mirdha (BMJ Global Health, 2025)
Background Scrub typhus, once known as tsutsugamushi fever and attributed to Rickettsia, has transformed into a growing public health concern. Despite its increasing incidence in India, comprehensive spatiotemporal analyses of scrub typhus have been lacking.Methods This study examines the prevalence of scrub typhus cases reported from 2003 to 2023, using available literature to provide a breakdown of cases by year and state in India, aiming to elucidate the disease’s spatiotemporal dynamics. The aetiological association of Orientia tsutsugamushi and scrub typhus is based on geographical, immunological and molecular genetic studies.Findings This analysis identified 47 650 cumulative cases of scrub typhus in India over the past two decades. The case fatality rate was 5% out of 35 243 cases. Variations in transmission dynamics and the Leptotrombidium vector’s competence may influence the disease’s distribution. Nonetheless, there has been a notable increase in infections since 2010, peaking in 2019 and 2022. Curtailing and containing such an upsurge can be daunting and requires an interdisciplinary public health approach. Further, there is heterogeneity in studies on general, gastrointestinal, pulmonary and inflammatory symptoms compared with studies on cardiac, hepatic, neurological and other symptoms. The Weil-Felix test was the most common diagnostic technique used, and doxycycline was the treatment for scrub typhus cases.Interpretations This meta-analysis can help policy-makers and researchers in India develop scrub typhus management and control policies.PROSPERO registration number CRD42024611771.